Treaty with the Pennsylvania Indians - Shoemaker, Benjamin
Treaty made with Pennsylvania Indians.
Photocopy.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Indians of North America -- Pennsylvania -- Treaties; Pennsylvania -- History -- Colonial period, ca. 1600-1775.